Penerapan Metode UCD (User Centered Design) dalam Perancangan Design UI/UX Website SMK - Putri, Belvana; Sutabri, Tata; Herdiansyah, M. Izman; Abdillah, Leon A. (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid development of digitalization has accustomed many people to using technology in their daily activities. Technological advancements have had a significant impact on various sectors, including business and education. A portal website designed using the User-Centered Design method aims to meet users' needs through UI and UX. This research focuses on designing the user interface and experience (UI/UX) of the SMK Negeri 2 Lahat portal website and producing a prototype of the UI/UX design using User-Centered Design.This research report offers several benefits, including providing recommendations for improving portal website design, enhancing user experience and satisfaction through better interface design, and contributing knowledge about design methods in portal website development. The research focuses on creating a portal website design for SMK Negeri 2 Lahat that is accessible to all, utilizing literature and user interviews. The development process involves comprehensive user needs analysis, literature review, interviews, and concept design.The research results show that UI/UX design for the portal website using Figma tools with the User-Centered Design method can be implemented at SMK Negeri 2 Lahat. The results of the Single Ease Question indicate a good indicator from the Likert scale calculation of 1-7.